2017
DOI: 10.18632/oncotarget.15888
|View full text |Cite
|
Sign up to set email alerts
|

HIF1α regulates single differentiated glioma cell dedifferentiation to stem-like cell phenotypes with high tumorigenic potential under hypoxia

Abstract: The standard treatment for Glioblastoma multiforme (GBM) is surgical resection and subsequent radiotherapy and chemotherapy. Surgical resection of GBM is typically restricted because of its invasive growth, which results in residual tumor cells including glioma stem cells (GSCs) and differentiated cells. Recurrence has been previously thought to occur as a result of these GSCs, and hypoxic microenvironment maintains the GSCs stemness also plays an important role. Summarizing traditional studies and we find man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 47 publications
3
41
0
Order By: Relevance
“…There is no doubt that the enhanced expression of CD133 may be due to the proliferation of CD133 + cells that exist in the unsorted cells; however, another possibility exists that these enhanced CD133 cells originate from differentiated cells through dedifferentiation. Actually, this phenomenon has been proved by our team recently, in this study we found cancer stem cells, including glioma, hepatom and lung cancer, can be induced through dedifferentiation in hypoxia 30 , 31 . In contrast, as an effective way to alleviate a hypoxic environment, hyperoxia promotes the sensitivity of glioma cells to TMZ by decreasing the expression of MGMT, ABCG2 and Ki67 and inducing a higher cell apoptosis rate, resulting in an extended survival time for glioma patients 15 , 16 , 18 , 19 , 32 .…”
Section: Discussionsupporting
confidence: 52%
“…There is no doubt that the enhanced expression of CD133 may be due to the proliferation of CD133 + cells that exist in the unsorted cells; however, another possibility exists that these enhanced CD133 cells originate from differentiated cells through dedifferentiation. Actually, this phenomenon has been proved by our team recently, in this study we found cancer stem cells, including glioma, hepatom and lung cancer, can be induced through dedifferentiation in hypoxia 30 , 31 . In contrast, as an effective way to alleviate a hypoxic environment, hyperoxia promotes the sensitivity of glioma cells to TMZ by decreasing the expression of MGMT, ABCG2 and Ki67 and inducing a higher cell apoptosis rate, resulting in an extended survival time for glioma patients 15 , 16 , 18 , 19 , 32 .…”
Section: Discussionsupporting
confidence: 52%
“…Prolonged hypoxia triggers the expression of CA-IX (21,22) and forms the immunohistochemically visualized regions of hypoxia. While in the center of hypoxia, due to the conditions of oxygen deficiency, several biomarkers are only expressed very low in the fringe, cells that directly border on hypoxic regions acquire resistance factors (10,11) and form stem cell and resistance regions. They gain resilience due to a more stable cell structure (intermediary filaments, e.g., GFAP, nestin, and vimentin), due to the improvement of coping strategies against stress (ALDH1), due to stabilization of the cell milieu (CA-IX) (23) and as a result of an increased migration capability.…”
Section: Discussionmentioning
confidence: 99%
“…From recently published data we know that hypoxia is an inductor of resistance factors in tumor cells and neoplastic tissue (10)(11)(12)(13). Regions of hypoxia (HReg) form our cluster 2.…”
Section: Regions Of Hypoxia (Hreg)mentioning
confidence: 99%
“…Hypoxia has also been shown to promote dedifferentiation of mature glioma cells into stem-like glioma stem cells (GSCs). Hypoxia induced single differentiated CD133-/CD15-/NESTIN-glioma cells into viable neurospheres through elevated expression of critical genes including SOX-2, OCT-4, KLF-4, NANOG, CD133, CD15, NESTIN and ABCG2 [54]. Interestingly, hypoxia induced CSC enrichment also resulted in increased tumourgenicity and mortality in vivo.…”
Section: Enrichment and Propagation Of Cancer Stem Cellsmentioning
confidence: 99%